A Rapid Reversed-Phase HPLC Method for Analysis of Trans-Resveratrol in PLGA Nanoparticulate Formulation. (16th February 2014) - Singh, Gurinder; Pai, Roopa S.
Abstract : A rapid reversed-phase high performance liquid chromatography (RP-HPLC) method was developed for the determination of trans -resveratrol ( t -RVT) in PLGA nanoparticle formulation. A new formulation of t -RVT loaded PLGA nanoparticles (NPs) with potential stealth properties was prepared by nanoprecipitation method in our laboratory. The desired chromatographic separation was achieved on a Phenomenex C18 column under isocratic conditions using UV detection at 306 nm. The optimized mobile phase consisted of a mixture of methanol: 10 mM potassium dihydrogen phosphate buffer (pH 6.8): acetonitrile (63 : 30 : 7, v/v/v) at a flow rate of 1 mL/min. The linear regression analysis for the calibration curves showed a good linear correlation over the concentration range of 0.025–2.0 μ g/ml, with determination coefficients, R 2, exceeding 0.9997. The method was shown to be specific, precise at the intraday and interday levels, as reflected by the relative standard deviation (RSD) values, lower than 5.0%, and accurate with bias not exceeding 15% and percentage recovery was found to be in the range between 94.5 and 101.2. The limits of detection and quantification were 0.002 and 0.007 μ g/ml, respectively. The method was successfully applied for the determination of t -RVT encapsulation efficiency.